PSYCHOGRAPHIC SEGMENTATION OF PRIVATE LABEL BRAND CONSUMERS: A STUDY OF LIFESTYLE, VALUES, AND SOCIO-DEMOGRAPHIC CORRELATES - Cyril Crasto (Journal of Informatics Education and Research, 2025)
This study explores psychographic segmentation among Private Label Brand (PLB) consumers according to lifestyle, values, and socio-demographic correlates. In this study, we delved into various determinants that significantly influence PLB buying behavior, focusing on consumer psychographics, socio-demographics, shop habits, and store image. The research employs statistical methods like chi-square tests, logistic regression, correlation analysis, and moderated regression analysis to examine various hypotheses. The study results show that socio-demographic factors such as age, income, and education significantly impact PLB buying decisions, while gender does not significantly impact. Psychographic traits, including lifestyle, values, and attitude, also play their role in embracing PLB. Consumer attitudes toward PLBs are different from those toward national brands, as the latter are viewed as more quality, service, convenience, and innovation, and PLBs as price. Perceived quality, price, and convenience collectively impact PLB purchase decisions, with quality emerging as the most significant factor. Nonetheless, store reputation does not play a mediating role between the PLB attributes and purchase. This implies consumer perception is stronger. The study provides practical tips for retailers and marketers to enhance their segmentation by reaching targeted groups, enhancing the value of PLB, and applying consumer psychographics. The study also highlights the need for PLB brands to enhance product innovation and maintain competitive prices in order to reach a diverse group of consumers. Future studies can examine other factors such as brand loyalty, advertising effectiveness, and internet activity to gain a deeper understanding of PLB consumer behavior within an evolving retail landscape.